2018
DOI: 10.1051/matecconf/201816202024
|View full text |Cite
|
Sign up to set email alerts
|

Production of lightweight Geopolymer concrete using artificial local lightweight aggregate

Abstract: Due to the rapid depletion of natural resources, the use of waste materials and by-products from different industries of building construction has been gaining increased attention. Geopolymer concrete based on Pozzolana is a new material that does not need the presence of Portland cement as a binder. The main focus of this research is to produce lightweight geopolymer concrete (LWGPC) using artificial coarse lightweight aggregate which produced from locally available bentonite clays. In this investigation, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In some cases, some of the pellets are fused at a temperature above 1200 °C for optimum properties [ 21 , 44 ]. Most of the previous research used a similar drying method prior to sintering [ 45 , 46 ]. Chen et al [ 47 ] also reported a similar method where the pellets undergo a drying stage, followed by preheating at 500 °C expanding temperature of a temperature between 1100 °C and 1150 °C for the sintering process.…”
Section: Manufacturing Of Lightweight Aggregatementioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, some of the pellets are fused at a temperature above 1200 °C for optimum properties [ 21 , 44 ]. Most of the previous research used a similar drying method prior to sintering [ 45 , 46 ]. Chen et al [ 47 ] also reported a similar method where the pellets undergo a drying stage, followed by preheating at 500 °C expanding temperature of a temperature between 1100 °C and 1150 °C for the sintering process.…”
Section: Manufacturing Of Lightweight Aggregatementioning
confidence: 99%
“…The sintered fly ash aggregate with bentonite added had a specific gravity of 1.57, while the sintered fly ash aggregate with glass powder added had a specific gravity of 1.60 at the temperature at 1200 °C [ 54 ]. Meanwhile, coarse aggregate manufactured from bentonite and water glass has a specific gravity of 1.63 at a temperature of 800 °C [ 46 ].…”
Section: Physical and Mechanical Properties Of Lightweight Aggregatementioning
confidence: 99%
See 1 more Smart Citation
“…Material density can be reduced by using lightweight and porous aggregates [ 19 , 20 ]. Concrete, including the geopolymer one, is considered light when its dry density is within the range of 800–2000 kg/m 3 [ 20 , 21 ]. Examples of aggregates that can be used to obtain geopolymeric materials with relatively high strength and low density are microspheres [ 22 , 23 , 24 , 25 , 26 , 27 ], vermiculite [ 28 , 29 ], granulated foam glass [ 30 , 31 , 32 ], expanded polystyrene (Styrofoam) [ 29 , 33 ], pumice [ 34 , 35 ], perlite [ 36 , 37 , 38 ], and other expanded materials, e.g., clay or glass [ 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research advances for the requirement for high-strength geopolymer can also be achieved, as in the study of Abbas et al [35], in which they worked on the development of high-strength lightweight geopolymer concrete, with strength conforming to around 36 MPa. Low calcium fly ash, along with alkali activators, were used as geopolymer precursors.…”
Section: Mechanical Properties Of Geopolymer Cement/concretementioning
confidence: 99%